Fabrication of self-assembled folate–biotin-quaternized starch nanoparticles as co-carrier of doxorubicin and siRNA. (November 2017) - Li, Liangping; Tao, Ruisong; Song, Mingming; Zhang, Yue; Chen, Kuanmin; Wang, Hui; Gong, Renmin
In this paper, the starch was firstly modified by quaternary reagent to obtain cationic starch. Then self-assembled folate–biotin-quaternized starch nanoparticles were prepared by a one-pot synthesis via N, N′-dicyclohexylcarbodiimide/N-hydroxysuccinimide/4-dimethylaminopyridine-mediated esterification reaction. The physicochemical properties of the prepared folate–biotin-quaternized starch nanoparticles were characterized. The average diameter of folate–biotin-quaternized starch nanoparticles was 109 nm with polydispersity index of 0.183 and zeta potential of 28.59 mV. The folate–biotin-quaternized starch nanoparticles were used as co-carrier of siRNA and doxorubicin with satisfactory drug loading capacity (6.98%) and encapsulation efficiency (69.66 %), and siRNA could be efficiently encapsulated at 40/1 weight ratio of doxorubicin/folate–biotin-quaternized starch nanoparticles to siRNA. The folate–biotin-quaternized starch nanoparticles could effectively protect siRNA from degradation of serum RNAase for up to 48 h. The release characteristics of doxorubicin and siRNA from folate–biotin-quaternized starch nanoparticles were studied in different pH environment and the release behaviors of two drugs were all pH sensitive. The folate–biotin-quaternized starch nanoparticles as a potential co-carrier of anticancer agents and gene drugs was expected to achieve future practical application in vitro and in vivo.